Estudo biomolecular de indivíduos soro-indeterminados para o retrovírus HTLV-I/II - Santos, Terezinha de Jesus Teixeira (2001)
The HTLV-I/II belongs to the Retroviridae family and Oncovirinae subfamily. Its genetic structure is similar to that of other mammalian retroviruses, with gag, pol, env and tax/rex regions. The gag region codes for pl9, p24 and pl 5 proteins; the pol region codes for the reverse transcriptase, RN Ase and integrase; the env region codes for the glycoproteins gp21 and gp46; and the pX region codes for the regulatory proteins tax (p40) and rex (p27). The HTLV-I/II is endemic in Central and West África, Caribbean, South America, Japan and Melanesia. In Brazil, its prevalence is of 0.46%. The molecular epide- miology shows that the HTLV-I is divided into the Ia (cosmopolitan), Ib (Central África) and Ic (Melanesia) subtypes, and HTLV-II into the lia, Ilb, He and Ild subtypes. This retrovirus is transmitted vertically (mother-to-child) and horizontally (sexual contact, blood transfusion and parenteral drugs use). The Tropical Spastic Paraparesis / HTLV-I-associated Myelopathy (TSP/HAM) and Adult T-cell Leukemia/Lymphoma (ATL) are their main associated patholo- gies. The laboratorial diagnosis of HTLV is done with screening (ELISA and parti- cle agglutination), confirmatory (Western blot, IFA, RIPA, and more recently INNO-LIA) and molecular (PCR, NASBA and bDNA) tests. Serological tests for HTLV infection are mandatory in some countries since 1986, and in Brazil since 1993. The results from blood banks have shown negative, positive and indeterminate results. Since the defínition of the seroindeterminate condition is important for blood banks and for the patienfs families, we intended to delineate a diagnostic, demographic and co-infection and risk factors association pictures of this condition as well as to analyze West ern blot protein pattems and isolated proteins with possible predictive meaning. For this, a preliminary analysis of prevalence of the seroindeterminate and ELISA reactive individuais in the general population of blood donors from the Hematology and Hemotherapy Center (HEMOCE) of Fortaleza City between 1997 and 2000 was done. Subsequently, a sample of 191 ELISA reactive individuais (118 WB seroindeterminates and 73 WB seropositives) from HEMOCE’s HTLV Unit was analyzed, with their previous ethical XX vii consent. This sample was diagnostically analyzed with ELISA, particle agglutination, West ern blot. INNO-LIA and PCR. For PCR, the tax/rex region was amplified. The results showed that the prevalence of seroindeterminate individuais in the general population of blood donors was of 1.64%o (0.16%), and the prevalence of the seropo- sitives for HTLV-I/II was of 1.36%o (0.13%). On the other hand, the prevalence of seroinde terminate individuais was of 21.91% in relation to the ELISA reactive population. The results of our sample showed that, diagnostically, the PCR evidenced in- fection in 41 seroindeterminate individuais studied, where 22.2% were positive and 77.8% were negative for HTLV-I/II. Moreover, the comparative analysis of PCR and INNO-LIA showed high concordance of results in both tests. The demographic analysis showed a trend of predominance of males among the WB seroindeterminate and PCR negative individuais as well as a trend of predominance of females among the HTLV-I/II seropositive individuais. In addition, mulattos predominate in both groups. As to age, seroindeterminate individuais are younger than the seropositive ones. The analysis of distribution of the seroindeterminate and HTLV-I/II seroposi- tives individuais as to the association with Co-Infections showed a higher prevalence of hepa- titis B and C for seropositive individuais, and a non-association with HTV, syphilis and Cha gas disease. The analysis of association with Risk Factors showed a high percentage of breast feeding similar for both groups, and a high percentage of blood transfusion and sexually- transmitted diseases (syphilis) for HTLV-I/II seropositive individuais. The analysis of the WB protein pattems and isolated proteins showed that among the WB seroindeterminates the most frequent pattems were p24, GD21 (7.6%) and pl9 + gp21 (or gp46) + one or more of the p26, p28, p32, p36, p53 proteins (25.5%), and the isolated p24 protein (55.0%). As to the seroindeterminate PCR negative individuais, the most frequent pattems were p28, p53, GD21 (9.4%) and pi9 + gp21 (or gp46) + one or more of the p26, p28, p32, p36, p53 proteins (31.2%), and the isolated gp21 protein (50.0%), pl9 (46.9%) and p28 (43.8%) proteins. As to the seroindeterminate PCR positive individuais, the most frequent pattems were p24, GD21 (50.0%) and pl9 + p24 + gp21 (or gp46) + one or more of the p26, p28, p32, p36, p53 proteins (77.8%), and the isolated p24 protein (100%). In conclusion, the study of our sample allowed us to show (1) a high preva lence of seroindeterminates in the population of ELISA HTLV-I/II reactive individuais from HEMOCE, (2) the efficacy of PCR as a diagnostic method for seroindeterminate definition, and INNO-LIA as an optional test, (3) a demographic profile of the seroindeterminate individuals, and (4) the identifícation of the WB protein pattems and isolated proteins which could be eventual candidates for predictive markers for HTLV-I/II infection positivity or negativity.